Opinion paper: Design criteria for documentation retrieval languages - Gebhardt, Friedrich; Stellmacher, Imant (Journal of the American Society for Information Science, 1978)
Query languages for document retrieval systems should be simple and easy to learn for the casual user; they should provide all conceivable facilities for the experienced user. These goals comprise the most serious contradictions that evolve between all the design criteria collected, compared, and evaluated in this paper. The proposed solution or, at least, relief to this conflict is to provide the user with a simple, clearly designed subset of the language that nevertheless includes all important query functions, while the additions to modify, shorten, improve, and extend it are left to the experienced user. It is stressed that the simple data formats available with most systems are insufficient; the need for more elaborate structures is substantiated. A point is made for a formal rather than a natural language for document retrieval.